Dimensions of Decision-Making Process Quality and Company Performance: A Study of Top Managers in Slovenia - Grušovnik, Damjan; Kavkler, Alenka (Naše gospodarstvo/Our economy, 2017)
This paper investigates the relationship between the dimensions of the decision- making process quality and company performance of top managers’ in Slovenia. We found out that companies whose managers exhibit an above-average dimension of openness of spirit in the quality of the decision making process, on average, have a higher stance on foreign markets as companies in which managers show a below-average open spirit. For the managers who work in companies that are present in foreign markets, we could confirm that there is a low/weak correlation between the dimension of effort of the decision-making process quality and the number of employees in a company.